Hukum Keluarga dalam Perspektif Perlindungan Anak - Musfiroh, Mayadina Rohmi (Fakultas Syariah, 2016)
This article points to trace the epistemological roots of early marriage to and reinforce the importance of Islamic Family law reform, particularly related to raising the minimum age of marriage. This article is the result of the research literature with a qualitative descriptive method using a theoretical approach maqashid al-sharia. Early marriage is the result of interpretation of scholars' to Q.S. Ath-Thalaq [65]: 4 which signaled the waiting period for those who do not menstruate. Islam does not provide ideal age limits in marriage. Marriages can be performed by the bride that has been not or already baligh if it has been qualified to do harmonious marriage. However, the scholars' proposed the opinions about puberty age limit for men and women and the permissibility of marrying someone in the age of the children. The decision to give an age limit in marriage for arising maslahah. Marriage age limit should be revised in view of the negative impacts arising from the early marriage models, such as women's reproductive health issues, financial problems of the family and divorce. Model of early marriage can no longer practiced because it is inconsistent with maqashid al-nikah that is to build a harmonious family.Artikel ini bertujuan melacak akar epistimologis perkawinan dini serta menguatkan argumentasi pentingnya pembaharuan hukum keluarga Islam, khususnya terkait menaikkanbatas minimal usia perkawinan. Artikel ini merupakan hasil penelitian kepustakaan dengan metode deskriptif-kualitatif dan menggunakan pendekatan teori maqashid al-syariah. Perkawinan dini merupakan hasil tafsir ulama’ terhadap Q.S. Ath-Thalaq [65]: 4 yang mengisyaratkan iddah bagi mereka yang belum haid. Islam tidak memberikan batasan umur ideal dalam pernikahan. Perkawinan dapat dilakukan oleh calon mempelai yang belum atau sudah baligh jika telah memenuhi syarat dan rukun pernikahan. Meskipun demikian, para ulama’ berbeda pendapat tentang batas usia baligh bagi laki-laki dan perempuan dan kebolehan menikahkan seseorang pada usia anak-anak. Umat Islam diperbolehkan memberikan batasan usia dalam perkawinan untuk menimbulkan kemaslahatan. Batas usia pernikahan perlu direvisi mengingat berbagai dampak negatif yang muncul akibat model pernikahan ini, misalnya masalah kesehatan reproduksi perempuan, persoalan ekonomi keluarga, hingga perceraian. Model perkawinan ini tidak dapat lagi dipraktikkan karena tidak sejalan dengan maqashid al-nikah yaitu membangun keluarga yang sakinah, mawaddah dan rahmah.